Żydzi na Kujawach w latach 1914-1922. Ujęcie porównawcze (Tabularium Historiae, 2021)
Kujawy from 1815 to 1918/1920 was within the borders of Russia (eastern Kujawy) and Prussia (western Kujawy). In both parts, Jewish communities were established that were demographically, culturally, politically and religiously different, the so-called German Jews and Eastern Jews (Ostjuden). After World War I, Kujawy found itself in reborn Poland. The Jews living there had to adapt to the new conditions and confront new challenges such as migration movements, democratization of life, integration and disintegration of individual Jewish communities, the spontaneous development of social, political and cultural life in the eastern part of Kujawy and their regression in the western part. The background was the national and religious changes and the anti-Semitism that was intensifying in the first years of independent Poland.